MON-368 A Case of Uremic Tumoral Calcinosis with Secondary Hyperparathyroidism - Mathew, Justin (J Endocr Soc, 2020)
Background: Uremic tumoral calcinosis is an uncommon clinical entity that can be seen in patients with end-stage renal disease, characterized by development of calcific deposits in the soft tissue. This condition can cause significant pain and impairment of mobility for patients. While it appears that elevation in calcium-phosphate product and hyperparathyroidism may each play a role in the development of these deposits, these conditions are neither necessary nor sufficient for this process to occur. As a result, the optimal treatment of this condition is not well-established. Case: A 50-year-old man with history of ESRD since 2015 secondary to autosomal dominant polycystic kidney disease on peritoneal dialysis, HTN, and secondary hyperparathyroidism presented to the emergency room with progressive right lateral hip pain, reaching the point where the patient could no longer ambulate. Exam demonstrated a thin man whose right hip was tender to palpation with limited range of motion, as well as a palpable, deep right upper leg mass. Laboratory findings were significant for a creatinine of 14.83mg/dL (n <1.5mg/dL), calcium of 9.1 mg/dL (n 8.5-10.5mg/dL), phosphate of 7.9mg/dL (n 2.5-4.5mg/dL), intact PTH of 1129pg/mL (n 15-65pg/mL), and 25-OH Vit D of 20.4ng/mL (n>30ng/mL). X-ray of the right femur demonstrated a 9cm calcified soft tissue lesion, which was not present on imaging 7 months earlier. Subsequent CT of the pelvis showed a cystic, multilobulated calcified mass in the right gluteus, measuring 6.1 x 3.5 x 7.5cm, consistent with tumoral calcinosis. Attempts to normalize his serum phosphorous level using treatment with phosphate binders or changes to his dialysate had failed previously, and the patient declined transitioning to hemodialysis. Nuclear medicine parathyroid scan demonstrated four-gland hyperplasia, and the decision was made to perform 3.5 gland parathyroidectomy. Two days post-operatively calcium had dropped to 7.7 mg/dL, phosphate to 6.8mg/dL, and intact PTH to 29pg/mL. Conclusions: Uremic tumoral calcinosis is a very rare but potentially debilitating consequence of end-stage renal disease that can be significantly detrimental to quality of life in patients with ESRD. Elevated calcium-phosphate product is frequently implicated in its development, and evidence exists that lowering these levels can lead to complete resolution of these lesions. However, in patients for whom medical therapy is not effective and who have concomitant secondary hyperparathyroidism, subtotal parathyroidectomy is a reasonable treatment option.